Correction: Florêncio et al. Synergistic Effects of Probiotics and Lifestyle Interventions on Intestinal Microbiota Composition and Clinical Outcomes in Obese Adults. Metabolites 2025, 15, 70 - Glauber Pimentel Florêncio; Analicy Rodrigues Xavier; Ana Catarina de Castro Natal; Lorena Prado Sadoyama; Geórgia das Graças Pena; Ralciane de Paula Menezes; Geraldo Sadoyama Leal; Lislei Jorge Patrizzi; Denise Von Dolinger de Brito Röder (Metabolites)
Because the corresponding authors found the odds ratio (OR) in the table to be imprecise and unnecessary [...]